The Role of Stakeholders in the Provision of Minimum Service Health Care in Wonosobo Regency - Munib Arrohmah; Antono Suryoputro; Budiyono (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Wonosobo regency is one of the districts with the lowest achievement of minimum service standards in the health sector in Central Java. In 2022, Wonosobo District could only achieve 16.67%. The implementation of a policy requires the cooperation of all stakeholders. The low achievement of Wonosobo District shows the lack of commitment of the local government and other stakeholders in efforts to provide health services according to minimum service standards. Objective: This study aims to identify the stakeholders involved and how their roles in the fulfilment of health services according to minimum service standards in Wonosobo district so that it can be an evaluation material for stakeholders in optimising efforts to fulfil minimum service standards. Method: This research uses a descriptive method with a qualitative approach. The research informants were identified using a purposive mechanism based on stakeholder involvement. Primary data collection in this research was conducted through in-depth interviews using tools such as interview guidelines, recording and note-taking equipment. Secondary data was obtained through legislative documents and derivative products issued by the Wonosobo District Government and its subordinate organisations, as well as literature reviews. Result: The results of the stakeholder identification show that there are 9 stakeholders involved, representing policy-making groups (Wonosobo District Parliament, Wonosobo District Secretariat, Wonosobo District Development Planning Agency, Wonosobo District Health Office), policy-implementing groups (District Health Office, PHC and health cadres) and support groups outside the system (sub-district government, village government and PKK cadres). Conclusion: Based on the mapping conducted, there are two categories of stakeholders in this study, namely key players and subjects. Wonosobo District Parliament, Wonosobo District Secretariat, Wonosobo District Development Planning Agency, Wonosobo District Health Office, and PHC are in the key player position. Health cadres, sub-district governments, village governments and PKK cadres are in the subject position.